2005
DOI: 10.1080/0141620042000336648
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐class interactive teaching and learning in religious education: transcripts from four primary classrooms

Abstract: The UK Qualifications and Curriculum Authority (QCA) documents for religious education indicate two distinct areas for study that may be characterised as teaching about the main faith traditions and tackling puzzling problems. This paper presents a detailed analysis of whole-class interactive teaching and learning in one session in each of four classrooms. The analysis will present two sessions with younger pupils and two with older pupils. The sessions analysed will reflect the QCA distinctions. The mode of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Studies of classroom talk also showed how teachers' overall aims affected pedagogical strategies. Eke et al (2005) studied whole-class interactive teaching in primary schools (see also Stern 2010), conducting discourse analysis according to two criteria: whether questions were specific to religious education or not, and whether they were teacher-centred or pupil-centred. Their analysis showed two broad patterns of questioning: 'puzzling questions' and 'understanding of the main religious traditions'.…”
Section: Pedagogical Approachesmentioning
confidence: 99%
“…Studies of classroom talk also showed how teachers' overall aims affected pedagogical strategies. Eke et al (2005) studied whole-class interactive teaching in primary schools (see also Stern 2010), conducting discourse analysis according to two criteria: whether questions were specific to religious education or not, and whether they were teacher-centred or pupil-centred. Their analysis showed two broad patterns of questioning: 'puzzling questions' and 'understanding of the main religious traditions'.…”
Section: Pedagogical Approachesmentioning
confidence: 99%